Let $\theta\in[0,1]$ be a constant and $f\in C^1[0,1] $. Show that $$\sum_k^{n-1}f\left(\frac{k+\theta} n\right)-n\int_0^1 f(x)\,dx$$

converges to $(\theta-\frac{1}{2})(f(1)-f(0))$, as $n\to\infty.$

\begin{align} & S_n=\sum_k^{n-1}f\left(\frac{k+\theta} n\right)-n\int_0^1 f(x)\,dx \\[10pt] ={} & n\sum_k^{n-1} \int_{k/n}^{(k+1)/n} \left( f \left(\frac{k+\theta} n\right)-f(x)\right) \, dx \\[10pt] = {} & n\sum_k^{n-1} \int_{k/n}^{(k+1)/n} \int_x^{(k+\theta)/n} f'(s) \, ds \, dx \\[10pt] = {} & n\sum_k^{n-1} \left( \int_{k/n}^{(k+\theta)/n} \int_x^{(k+\theta)/n}-\int_{k+\theta/n}^{(k+1)/n} \int_{(k+\theta)/n}^x \right)f'(s)\,ds\,dx \end{align}

\begin{align} & n\sum_k^{n-1} \int_{k/n}^{(k+1)/n} \int_x^{(k+\theta)/n} f'(s) \, ds \, dx \\[10pt] = {} & n\sum_k^{n-1} \left( \int_{k/n}^{(k+\theta)/n}\int_x^{(k+\theta)/n}-\int_{k+\theta/n}^{(k+1)/n} \int_{(k+\theta)/n}^x \right) f'(s) \, ds \, dx \end{align}

\begin{align}\int_{k/n}^{(k+\theta)/n}\int_x^{(k+\theta)/n} f'(s) \, ds \, dx=\int_{k/n}^{(k+\theta)/n}\int_{(k)/n}^s f'(s) \, ds \, dx=\int_{k/n}^{(k+\theta)/n}f'(s)(s-\frac{k}{n}) \, ds \int_{k+\theta/n}^{(k+1)/n}\int_{(k+\theta)/n}^x f'(s) \, ds \, dx=\int_{k+\theta/n}^{(k+1)/n}\int_s^{(k+1)/n} f'(s) \, ds \, dx=\int_{k+\theta/n}^{(k+1)/n}f'(s)(\frac{k+1}{n}-s) \, ds\end{align}

Therefore \begin{align} \sum_k^{n-1} \int_{k/n}^{(k+1)/n} f'(s)\phi_k(s) \, ds \end{align}

where \begin{align} \phi_k(s)=ns-k-\begin{cases} 0, & \mbox{ if }(k\leqslant ns <k+\theta)\\1, & \mbox{ if }k+\theta\leqslant ns <k+1\end{cases}\end{align},

Denoting by $\{x\}$ the fractional part of $x$ and noticing that $k=[ns]$ for $k\leqslant ns\leqslant k+1$, we see that $\phi_k(s)=g(ns)$, where

\begin{align}g(x)=\{x\}-\begin{cases} 0, & \mbox{ if }(\{x\}<\theta)\\1, & \mbox{ if }(\{x\}\geqslant \theta)\end{cases}=\{x-\theta\}+\theta-1\end{align}

is a piecewise linear periodic function of period 1.Any piecewise continuous periodic function $g(x)$, we conclude that \begin{align}S_n=\int_0^1 f'(x)g(nx)dx\to \mathscr{M}_[0,1](g)\times \int_0^1 f'(x) dx=(\theta-\frac{1}{2})(f(1)-f(0))\end{align} as $n\to\infty$ because $f'\in\mathscr{C}_[0,1]$


I do not understand what the author does when it is defined $g(x)=\{x\}-\begin{cases} 0, & \mbox{ if }(\{x\}<\theta)\\1, & \mbox{ if }(\{x\}\geqslant \theta)\end{cases}=\{x-\theta\}+\theta-1$ Where does this come from? How did he derive it?

How does the author prove \begin{align}S_n=\int_0^1 f'(x)g(nx)dx\to \mathscr{M}_[0,1](g)\times \int_0^1 f'(x) dx=(\theta-\frac{1}{2})(f(1)-f(0))\end{align}

Where did $\sum_{k=0}^{n-1}$ go to?

Thanks in advance!

  • $\begingroup$ Do you see how the first part, $$g(x) = \lbrace x\rbrace - \begin{cases} 0 &\text{if } \lbrace x\rbrace < \theta \\ 1 &\text{if} \lbrace x\rbrace \geqslant \theta \end{cases}$$ (it must be $\lbrace x\rbrace$ instead of $\lvert x\rvert$ in the first branch, somebody at some point misread a brace for a vertical bar) comes from $\phi_k(s)$? The second equality just uses $$\lbrace x - y\rbrace = \begin{cases} \lbrace x\rbrace - y &\text{if } \lbrace x\rbrace \geqslant y \\ \lbrace x\rbrace + (1-y) &\text{if } \lbrace x\rbrace < y \end{cases}$$ for $0 \leqslant y < 1$. $\endgroup$ Aug 20, 2018 at 12:04
  • $\begingroup$ I do not understand how the first part comes from $\phi_k(s)$. I have no clue whatsoever of how the author proceed on that regard. Concerning $\{\}$ instead of $||$, you are right. I have just corrected it. That was a typo of mine. Thanks for your reply. I would be glad if you told me how the indicator function on this case is derived. $\endgroup$ Aug 20, 2018 at 12:17
  • $\begingroup$ For $\frac{k}{n} \leqslant s < \frac{k+1}{n}$ we have $\lbrace ns\rbrace = ns - k$, for $k = \lfloor ns\rfloor$ then. And $k \leqslant ns < k + \theta$ is equivalent to $0 \leqslant ns - k < \theta$, which is $\lbrace ns\rbrace < \theta$. But I'm not sure what exactly you don't understand, so I'm not sure whether what I've said before helps or misses the point. $\endgroup$ Aug 20, 2018 at 12:24
  • $\begingroup$ @DanielFischer I still do not understand where the $x$ comes from. $\endgroup$ Aug 20, 2018 at 17:59
  • $\begingroup$ @DanielFischer I do not know if I was clear. My doubt arises at the point the author begins to define the function $g$. $\endgroup$ Aug 20, 2018 at 18:38

1 Answer 1


You can simplify things by noting the expression equals

$$\tag 1 \sum_{k=0}^{n-1}[f(k/n+\theta/n)- f(k/n)] + \sum_{k=0}^{n-1}f(k/n)- n\int_0^1 f.$$

By the MVT, the first sum in $(1)$ equals

$$\sum_{k=0}^{n-1}f'(c(k,n))\cdot (\theta/n) = \theta\sum_{k=0}^{n-1}f'(c(k,n))\cdot (1/n).$$

This converges to $\theta\int_0^1 f' =\theta(f(1)-f(0)).$

The rest of $(1)$ equals

$$\tag 2 n \left (\sum_{k=0}^{n-1}\int_{k/n}^{(k+1)/n}[f(k/n)-f(x)]\,dx\right ).$$

For $n$ large we expect $f(x) \approx f(k/n) +f'(k/n)(x-(k/n))$ for $x$ in the $k$th interval. Let's just brazenly insert that into $(2).$ We get

$$n \left (-\sum_{k=0}^{n-1}\int_{k/n}^{(k+1)/n}f'(k/n)(x-(k/n))\,dx \right )$$ $$ = n \left (-\sum_{k=0}^{n-1}f'(k/n)(1/(2n^2)) \right ) = -(1/2)\sum_{k=0}^{n-1}f'(k/n)(1/n). $$

The last expression $\to -(1/2)\int_0^1 f' = -(1/2)f(1)-f(0)).$ So this looks very good. All we need to verify is that the approximations $f(x) \approx f(k/n) +f'(k/n)(x-(k/n))$ are good enough. This follows from the uniform continuity of $f'.$ I'll leave this verification to the reader for now.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.